Comparison Between Alvarado Score and Paediatric Appendicitis Score in Diagnosing Acute Appendicitis in Children - Rajbhandari, Bikesh; Dahal, Geha Raj; Pokharel, Rameshwar Prasad (Journal of Nepal Paediatric Society, 2020)
Introduction: Acute appendicitis is the most common atraumatic surgical emergency in childhood. The accurate diagnosis of acute appendicitis is not always easy. Alvarado score (AS) and paediatric appendicitis score (PAS) are commonly used tools to assist diagnosis. This study compares the diagnostic accuracy between AS and PAS. Methods: A prospective study was conducted from September 2016 to September 2017 in Paediatric Surgery Unit of Tribhuvan University Teaching Hospital. All eligible patients (children up to 16 years) who were operated for acute appendicitis were included. AS and PAS were calculated for all patients preoperatively. Final diagnosis of acute appendicitis was based on histopathological examination and labeled as ‘appendicitis’ or ‘no appendicitis’. A cut off score of 7 for AS and 6 for PAS was compared with ‘appendicitis’ or ‘no appendicitis’ group. Results: A total of 70 patients were included in the study. Sixty five (93%) were histologically proven acute appendicitis and five (7%) were no appendicitis. The sensitivity, specificity, PPV, NPV and accuracy of AS were 89%, 40%, 95%, 22% and 85% respectively. For PAS, sensitivity, specificity, PPV, NPV and accuracy was 97%, 40%, 95.5%, 50% and 92% respectively. On Receiver Operating Characteristic curve, ‘area under curve’ of AS was 0.64 and that of PAS was 0.84. It was not statistically significant (p = 0.152). Conclusions: There was no statistical significant difference between AS and PAS for diagnosing acute appendicitis.